CYTOLOGICAL ALTERATIONS IN TAL OF RANA TIGERINA DURING METAMORPHOSIS - SHINDE, P.A.; SAWANT, V.A. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
The tadpole tail, which is twice as long as the body and serves as the main locomotory organ of the aquatic tadpole, gradually regresses as the typical tetrapod limbs develop. Definite detectable changes of tail degeneration occur during the later stages of metamorphosis, broadly classified as metamorphic climax. It was observed that both, spontaneously degenerating and thyroid hormone induced tail exhibit the same sequence of structural transitions.